Preclinical Safety Considerations for Biosimilars - Rao, Koppal Suryanarayana (Biology, Engineering, Medicine and Science Reports)
It is now a foregone conclusion that the new frontier of biomedical research lies in biologics, which hold the potential to yield, over time, effective treatments for conditions or diseases hitherto considered incurable or untreatable. On the scale of medical development, biologics are a fairly recent innovation and the majority of them are still under patent protection. The global outlook for biologics is positive and it is estimated that approximately two-dozen biological products with global sales of more than $67 billion will come off patent by 2020. Advances in biotechnology and the end of patent exclusivity have resulted in burgeoning opportunities for cost-effective followon biologics, commonly known as ‘biosimilars’, to enter the market.